Partisipasi Masyarakat dalam Pelestarian Cagar Budaya di Kawasan Ampel Surabaya - Dimas Okky Fareza; Agus Subianto (Public Administration Dept, Faculty of Social and Political Science, 2022)
The aim of this study was to determine the involvement of the Ampel community in preserving the cultural heritage of the Ampel religious tourist site. This study uses a qualitative method with a case study approach. Techniques for collecting data through observations, interviews, and documentation. This study analyzes using the theory of participation (Uphoff, 2011) including decision making, implementation participation, benefit participation and evaluation participation. The results of the analysis show that community participation in the preservation of cultural heritage in the Ampel area is suboptimal because the Ampel Takmir Mosque Foundation engages in self-determination without government or government intervention. other interested parties. Community participation in the assessment does not include the full participation of the community. However, participating in its implementation requires the participation of local residents as servants of Sunan, both in the clean field and in the safe field. Meanwhile, Ampel UPTD Religious Tourism Organization run by Surabaya City Government is limited to managing kiosks and parking spaces for visitors. In terms of profit sharing, the community can enjoy the physical buildings of the mosque and the mausoleum as a means of worship and pilgrimage, and can also enjoy Arabic cuisine and souvenirs. Arabic concept. It is hoped that the Ampel Mosque Foundation and the Surabaya City Government can work together to increase the survival of cultural heritage preservation in the Ampel Religious Tourist Area in the future